Стан та перспективи розвитку аграрного сектору економіки України в умовах євроінтеграції - Куделя, Євгеній Віталійович; Kudelia, Yevhenii (ЦНТУ, 2022)
В роботі досліджено сутність агропромислового комплексу України, місце в ньому аграрного сектору економіки та еволюцію думок вчених щодо змісту цих економічних категорій. Обґрунтовано основи розвитку підприємств аграрного сектору економіки в умовах євроінтеграції. Визначено тенденції розвитку та функціонування аграрного сектору економіки України в контексті міжнародної продовольчої безпеки та євроінтеграції. Виконано макроекономічний аналіз ефективності господарювання аграрного сектору економіки України. Окреслено напрями розвитку аграрного сектору економіки України в умовах євроінтеграції. Досліджено шляхи зближення державної аграрної політики України із Спільною аграрною політикою Європейського Союзу. Визначено пріоритети зовнішньоекономічної діяльності аграрного сектору економіки України. Вивчено досвід господарювання зарубіжних країн в аграрному секторі. Визначено та обґрунтувано перспективні орієнтири та сценарії розвитку аграрного сектору економіки України в умовах євроінтеграції. The work examines the essence of the agro-industrial complex of Ukraine, the place of the agrarian sector in the economy, and the evolution of the scientific opinions regarding the content of these economic notions. The grounds of theenterprises development in the agrarian sector of the economy in the conditions of European integration are defined. The development and functioning trends of the agricultural sector of Ukraine's economy in the context of international food security and European integration are determined. The macroeconomic analysis of theagrarian sector management efficiency of the Ukrainian economy has been performed. The ways for the development of the agrarian sector in Ukraine under the European integration are outlined. Ways of convergence between the state agrarian policy of Ukraine and the Common Agrarian Policy of the European Union have been studied. The management experience of foreign countries in the agricultural sector has been studied. Prospective guidelines for the development of the agricultural sector of Ukraine's economy in the conditions of European integration have been defined and substantiated.
State and Prospects of the Agricultural Sector Development in Ukraine in the Conditions of European Integration
Keywords: євроінтеграція; аграрний сектор; розвиток аграрного сектору економіки; зона вільної торгівлі; експорт; імпорт; European integration; agricultural sector; development of the agricultural sector of the economy; free trade zone; export; import